Predicting vaping uptake, vaping frequency and ongoing vaping among daily smokers using longitudinal data from the International Tobacco Control (ITC) Four Country Surveys. (21st January 2019) - Chan, Gary; Morphett, Kylie; Gartner, Coral; Leung, Janni; Yong, Hua‐Hie; Hall, Wayne; Borland, Ron
Abstract: Aim: To assess (1) how far smoking patterns, depression and smoking‐related beliefs and intentions predict vaping uptake, current vaping and vaping frequency among daily smokers; and (2) how far the aforementioned predictors and baseline vaping frequency predict current vaping among those who reported ever vaped. Design: Analysis of data from six waves of a longitudinal survey over 8 years. Longitudinal associations between predictors and outcomes were examined using multi‐level models. Setting: United Kingdom, United States, Canada and Australia. Participants: A total of 6296 daily smokers (53% females) who contributed data to at least two consecutive survey waves. Measurements: The outcome variables were vaping uptake, vaping frequency and current vaping at follow‐up. The key predictor variables, measured in previous waves, were time to first cigarette, cigarettes smoked per day, depressive symptoms, intention to quit smoking, quitting self‐efficacy and worry about adverse health effects of smoking. Findings: Number of cigarettes smoked daily was associated with (1) subsequent vaping uptake [odds ratio (OR) = 1.69, 95% confidence interval (CI) = 1.19, 2.39 for 30+ cigarette per day; reference category: 0–10 cigarettes] and (2) a higher frequency of current vaping (OR = 1.97, 95% CI = 1.36, 2.85 for 30+ cigarettes). Intention to quit was associated with a higher frequency of current vaping (OR = 1.48, 95% CI = 1.21, 1.82). Among those who reported ever vaped, higher baseline vaping frequency (OR = 11.98, 95% CI = 6.00, 23.93 for daily vaping at baseline; reference category: vaped less than monthly) predicted current vaping. Conclusion: Among daily smokers, amount smoked and intention to quit smoking appear to predict subsequent vaping uptake. Vaping frequency at baseline appears to predict current vaping at follow‐up.